Post-translational regulation of Cas9 during G1 enhances homology-directed repair - Gutschner, Tony; Hämmerle, Monika (Cell reports, 2016)
CRISPR/Cas9 induces DNA double-strand breaks that are repaired by cell-autonomous repair pathways, namely, non-homologous end-joining (NHEJ), or homology-directed repair (HDR). While HDR is absent in G1, NHEJ is active throughout the cell cycle and, thus, is largely favored over HDR. We devised a strategy to increase HDR by directly synchronizing the expression of Cas9 with cell-cycle progression. Fusion of Cas9 to the N-terminal region of human Geminin converted this gene-editing protein into a substrate for the E3 ubiquitin ligase complex APC/Cdh1, resulting in a cell-cycle-tailored expression with low levels in G1 but high expression in S/G2/M. Importantly, Cas9-hGem(1/110) increased the rate of HDR by up to 87% compared to wild-type Cas9. Future developments may enable high-resolution expression of genome engineering proteins, which might increase HDR rates further, and may contribute to a better understanding of DNA repair pathways due to spatiotemporal control of DNA damage induction.